Using List of Values as Base of Beer Consumer Segmentation Based on Their Lifestyle-Case of Study City of Pristina - Begunca, Arsim (European Journal of Economics and Business Studies, 2016)
When studying lifestyles, value is an essential element in defining of internal status for individual. For almost as long as values were studied in consumer’s behavior, methodology was in favor of researchers. Human values have found increasing use as the basis of market segmentation. In our study using the LOV scale as a base for beer consumer segmentation based on lifestyle, we have managed to divide these customers/consumers in three segments. These segments are sports - entertainment segment; traditional-family segment and health-safety segment. Thus several hypotheses generated that have been confirmed. For Data Analysis program named Statistical Package for Social Science ( SPSS version 20) has been used. This study used descriptive analysis, factorial analysis, independent samples, T-test, one way between groups ANOVA and cluster analysis.
Keywords: Lifestyle, respondent, beer consumer, List of values.